LITERATURE REVIEW: EFFECTIVENESS OF HONEY, CURCUMA AND TURMERIC FOR CHILD HEALTH - Marni, Marni; Firdaus, Insanul; Wahyuningsih, Wahyuningsih; Soares, Domingos; Tahta Raharja, Muhammad Langlang; Siska Savitri, Dessy Nourma (LPPM Universitas Duta Bangsa Surakarta, 2023)
Introduction: Malnutrition causes children to experience health problems in the short and long term. The research method used is a literature review. Checklist Prisma has been used for registration of titles, abstracts, full texts and methodologies with the keywords Honey AND Turmeric AND Curcuma AND Child Health. The computerized databases that have been used to search for articles in this study are Science Direct, Pubmed, ProQuest and Google Scholar. The journals published in the period 2013 to 2023. Result: There were 8 articles that were relevant to the search keywords used. Foods that contain lots of bioactive compounds such as Curcuma Zanthorrhiza, turmeric / Curcuma Ionga, honey are very beneficial for health, especially for children's growth and development, preventing infections, preventing various diseases. Conclusion: Curcuma Zanthorrhiza, turmeric / Curcuma Ionga, honey improve health, increase body weight, prolong life, prevent infection, prevent various diseases, increase nutrients such as carbohydrates, protein, fat.